219 Comparing Sleep Amount and Quality for People Working from Home with and Without Minor Dependents during the COVID-19 Pandemic. (3rd May 2021) - Cordoza, Makayla; Kaizi-Lutu, Marc; Jones, Christopher; Mange, Ami; Dinges, David
Abstract: Introduction: The global pandemic due to the novel coronavirus (COVID-19) has had unprecedented effects on society, in particular for those who are also working with children in the household. The aim of this analysis was to evaluate sleep amount and sleep quality during the COVID-19 pandemic compared to before COVID-19 for those working from home with minor household dependents. Methods: We developed the "Anonymous Survey on Confinement during the COVID-19 Pandemic", a national survey for individuals ≥18 years of age hosted on the Penn Medicine Clinical Research website from May 16th to November 11th, 2020. This 200 question survey captured demographics and multiple dimensions of health and well-being, including stress, sleep, eating behaviors, and coping activities. Respondents who indicated they were working from home were stratified by whether they were living with ≥1 minor dependent vs no dependents. Separate ordinal logistic regression models were used to evaluate associations between living with a minor dependent and sleep amount (less, same, more) and disturbed quality (none, less, same, more) during, compared to before, COVID-19 controlled for age, sex, ethnicity, and annual income. Results: A total of 232 respondents (n=182 no dependents, n=50 dependents, 84.9% Caucasian) reported working from home, the majority of which had been in confinement (95.7%). Respondents with dependents were younger (mean age 38.9±13.5 vs 47.4±18.0, p=0.002) and mostly female (86% vs 76.9%, p=0.03). On average, reported days worked/week (3.5±2.4 days) and hours worked/day (5.5±4.17 hours) were similar regardless of dependents. Comparing those without to those with minor dependents, there were no significant differences in log odds of getting enough sleep (β=-0.38, p=0.25) or worse sleep quality (β=0.41, p=0.22) during the COVID-19 pandemic compared to before COVID-19. Respondents with dependents reported a higher log odds of taking longer to fall asleep during COVID-19 (β=0.71, p=0.045), and higher stress (β=-0.65, p=0.04). Conclusion: In this mostly Caucasian female sample of people working from home, having minor dependents in the household did not significantly impact sleep amount or quality compared to no minor household dependents. However, respondents with dependents reported longer time to fall asleep and were more stressed. Support (if any): MC/CJ are supported by NHLBI (T32 HL007713).